PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN PADA PERBANKAN - Susilowati; Pengwi; Yusiresita Pajaria; Edi Triwibowo; Vieronicha Lyu Sipanghona (Universitas Tangerang Raya, 2021)
This study was investigated to see the effect of Institutional Ownership and Audit Committee on Firm Value in Islamic banking in 2016-2019. The sample of this study, the researchers used all Islamic banking companies during the 2016-2019 period totaling 13 companies. The data used using secondary data obtained from the website of Islamic banking companies. Based on the analysis results show that the variable of institutional ownership has an effect on firm value and the audit committee has an effect on the dependent variable of firm value.